Learn more about

Refine search

Results (displaying matches 1-50 of 63312) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
196.a.21952.1 196.a \(y^2 + (x^2 + x)y = x^6 + 3x^5 + 6x^4 + 7x^3 + 6x^2 + 3x + 1\) $E_1$ 0
249.a.249.1 249.a \(y^2 + (x^3 + 1)y = x^2 + x\) $\mathrm{USp}(4)$ 0
249.a.6723.1 249.a \(y^2 + (x^3 + 1)y = -x^5 + x^3 + x^2 + 3x + 2\) $\mathrm{USp}(4)$ 0
277.a.277.1 277.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^2 - x\) $\mathrm{USp}(4)$ 0
277.a.277.2 277.a \(y^2 + y = x^5 - 9x^4 + 14x^3 - 19x^2 + 11x - 6\) $\mathrm{USp}(4)$ 0
295.a.295.1 295.a \(y^2 + (x^3 + 1)y = -x^2\) $\mathrm{USp}(4)$ 0
295.a.295.2 295.a \(y^2 + (x^2 + x + 1)y = x^5 - 40x^3 + 22x^2 + 389x - 608\) $\mathrm{USp}(4)$ 0
349.a.349.1 349.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^3 - x^2\) $\mathrm{USp}(4)$ 0
353.a.353.1 353.a \(y^2 + (x^3 + x + 1)y = x^2\) $\mathrm{USp}(4)$ 0
388.a.776.1 388.a \(y^2 + (x^3 + x + 1)y = -x^4 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
389.a.389.1 389.a \(y^2 + (x^3 + x)y = x^5 - 2x^4 - 8x^3 + 16x + 7\) $\mathrm{USp}(4)$ 0
389.a.389.2 389.a \(y^2 + (x + 1)y = x^5 + 2x^4 + 2x^3 + x^2\) $\mathrm{USp}(4)$ 0
394.a.394.1 394.a \(y^2 + (x^3 + x)y = 2x^5 + x^4 - 12x^3 + 17x - 9\) $\mathrm{USp}(4)$ 0
394.a.3152.1 394.a \(y^2 + (x + 1)y = -x^5\) $\mathrm{USp}(4)$ 0
400.a.409600.1 400.a \(y^2 = x^6 + 4x^4 + 4x^2 + 1\) $E_1$ 0
427.a.2989.1 427.a \(y^2 + (x^3 + 1)y = x^5 - x^4 - 5x^3 + 4x^2 + 4x - 4\) $\mathrm{USp}(4)$ 0
461.a.461.1 461.a \(y^2 + x^3y = x^5 - 3x^3 + 3x - 2\) $\mathrm{USp}(4)$ 0
461.a.461.2 461.a \(y^2 + y = x^5 - x^4 - 39x^3 + 10x^2 + 272x - 306\) $\mathrm{USp}(4)$ 0
464.a.464.1 464.a \(y^2 + (x + 1)y = -x^6 - 2x^5 - 2x^4 - x^3\) $\mathrm{USp}(4)$ 0
464.a.29696.1 464.a \(y^2 + (x + 1)y = 8x^5 + 3x^4 - 4x^3 - 2x^2\) $\mathrm{USp}(4)$ 0
464.a.29696.2 464.a \(y^2 + xy = 4x^5 + 33x^4 + 72x^3 + 16x^2 + x\) $\mathrm{USp}(4)$ 0
472.a.944.1 472.a \(y^2 + (x^2 + 1)y = x^5 - x^4 - 2x^3 + x\) $\mathrm{USp}(4)$ 0
472.a.60416.1 472.a \(y^2 + (x + 1)y = 8x^5 + 5x^4 + 4x^3 + 2x^2\) $\mathrm{USp}(4)$ 0
523.a.523.1 523.a \(y^2 + (x + 1)y = x^5 - x^4 - x^3\) $\mathrm{USp}(4)$ 0
523.a.523.2 523.a \(y^2 + xy = x^5 - 31x^4 - 110x^3 + 21x^2 - x\) $\mathrm{USp}(4)$ 0
555.a.8325.1 555.a \(y^2 + (x + 1)y = 3x^5 - 2x^4 - 4x^3 + x^2 + x\) $\mathrm{USp}(4)$ 0
574.a.293888.1 574.a \(y^2 + (x^2 + x)y = x^5 - x^4 - 3x^2 + x + 1\) $\mathrm{USp}(4)$ 0
576.b.147456.1 576.b \(y^2 = x^6 + 2x^4 + 2x^2 + 1\) $E_1$ 0
587.a.587.1 587.a \(y^2 + (x^3 + x + 1)y = -x^2 - x\) $\mathrm{USp}(4)$ 1
597.a.597.1 597.a \(y^2 + y = x^5 + 2x^4 + 3x^3 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
603.a.603.1 603.a \(y^2 + (x^2 + 1)y = x^5 + 8x^4 + 4x^3 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 0
603.a.603.2 603.a \(y^2 + (x^2 + 1)y = x^5 - x^3 + x\) $\mathrm{USp}(4)$ 0
604.a.9664.1 604.a \(y^2 + (x^2 + x + 1)y = 4x^5 + 9x^4 + 48x^3 - 4x^2 - 53x - 21\) $\mathrm{USp}(4)$ 0
604.a.9664.2 604.a \(y^2 + (x^3 + 1)y = -x^4 + x^3 + x^2 - x\) $\mathrm{USp}(4)$ 0
644.b.14812.1 644.b \(y^2 + (x^3 + 1)y = x^5 - x^4 - 4x^3 + 5x^2 - x - 1\) $\mathrm{USp}(4)$ 0
676.b.17576.1 676.b \(y^2 + (x^2 + x)y = -x^6 + 3x^5 - 6x^4 + 6x^3 - 6x^2 + 3x - 1\) $E_1$ 0
688.a.2752.1 688.a \(y^2 + y = 2x^5 - 5x^4 + 4x^3 - x\) $\mathrm{USp}(4)$ 0
688.a.704512.2 688.a \(y^2 = 2x^5 - 7x^4 - 8x^3 + 2x^2 + 4x + 1\) $\mathrm{USp}(4)$ 0
688.a.704512.1 688.a \(y^2 = 2x^5 + 4x^3 + x^2 + 2x + 1\) $\mathrm{USp}(4)$ 0
691.a.691.1 691.a \(y^2 + (x + 1)y = x^5 - x^3 - x^2\) $\mathrm{USp}(4)$ 0
704.a.45056.1 704.a \(y^2 + y = 4x^5 + 4x^4 - x^3 - 2x^2\) $\mathrm{USp}(4)$ 0
708.a.2832.1 708.a \(y^2 + (x^2 + x + 1)y = x^5\) $\mathrm{USp}(4)$ 0
708.a.19116.1 708.a \(y^2 + (x^3 + 1)y = -x^5 + 4x^2 + 4x - 1\) $\mathrm{USp}(4)$ 0
708.a.181248.1 708.a \(y^2 + (x^3 + 1)y = -x^6 - 4x^5 + 9x^4 + 48x^3 - 41x^2 - 98x - 36\) $\mathrm{USp}(4)$ 0
709.a.709.1 709.a \(y^2 + xy = x^5 - 2x^2 + x\) $\mathrm{USp}(4)$ 0
713.a.713.1 713.a \(y^2 + (x^3 + x + 1)y = -x^5 - x\) $\mathrm{USp}(4)$ 1
713.b.713.1 713.b \(y^2 + (x^3 + x + 1)y = -x^4\) $\mathrm{USp}(4)$ 0
731.a.12427.1 731.a \(y^2 + (x^3 + x^2)y = x^5 + 2x^4 - x - 3\) $\mathrm{USp}(4)$ 0
741.a.28899.1 741.a \(y^2 + (x + 1)y = -3x^5 - x^4 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
743.a.743.1 743.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^2\) $\mathrm{USp}(4)$ 1
Next

Download all search results for